Hubungan Ketahanan Pangan dengan Status Gizi Balita di Kota Parepare - Usman, Usman; Hasnah, Hasnah (Jurnal Kesehatan Nusantara (JKN), 2025)
This study aims to determine the relationship between food security and the nutritional status of toddlers in Parepare City. This study used a quantitative research design with a cross-sectional approach. The study sample consisted of 100 households with toddlers randomly selected in 5 sub-districts in Parepare City. Food security data was measured using the Food Insecurity Experience Scale (FIES), while toddler nutritional status was measured using anthropometric indicators (weight/height and weight/age). Data analysis was conducted using the chi-square test to examine the relationship between food security variables and toddler nutritional status. The results showed a significant relationship between food security and toddler nutritional status in Parepare City (p-value <0.05). The worse the food security, the higher the likelihood of toddlers experiencing malnutrition. This study provides recommendations for local governments to improve household food security through economic empowerment programs and nutrition education